Peran Etika Ekonomi Islam dalam Perdagangan Internasional: Telaah Kritis atas Pemikiran Imam Al-Ghazali - Yulianingsih, Dwi Indriastuti; Mohammad Sapta Heriyawan (Jurnal Ilmiah Ekonomi Islam, 2025)
International trade is a global phenomenon that cannot be avoided by any country. In Islamic economics, trade activities are regulated based on the principles of justice, welfare, and prohibition of exploitation. This article aims to examine Imam Al-Ghazali's views on the principles and role of the state in international trade and its impact on the economic independence of the people. Al-Ghazali views that the state must play an active role in maintaining market stability, supporting local businesses, and avoiding dependence on other countries. This article uses a literature study approach to the main works of Al-Ghazali and other Islamic economic thinkers. The findings show that international trade from an Islamic perspective is not just an economic tool, but a moral and social instrument that requires ethical control from the state and market players.